The Role Of NGO In Ecotourism Development In The Bukit Lawang Tourism Village Plantation, North Sumatra - Lubis, Muhammad Rizki (Politeknik Internasional Bali, 2023)
This study examines and analyzes the participation of NGOs in tourism development in Bukit Lawang Tourism Village Plantation. This study used a descriptive-qualitative method with data collection tools in the form of observation and interview. The results of this study describe that the role of NGOs in developing ecotourism in Bukit Lawang has been carried out by Project Wings by carrying out activities that have succeeded in collecting 325 kg of waste. The Kelas Hijau Institute has also conducted weekly class activities which are held every week for around 60 to 100 local children or classes about the environment and English education for children aged 5 to 12 years. At the Environmental Center stage, they have a contribution in providing information and building cooperation with community protection in efforts to conserve and manage the environment wisely as well as advocating for environmental preservation. The success of the role of NGOs in tourism development is also influenced by the appropriate expertise in terms of quality, honesty and consistency of each party involved.